New therapeutic strategies targeting D1-type dopamine receptors for neuropsychiatric disease - Kim, Young-Cho (Front Biol (Beijing), 2015)
The neurotransmitter dopamine acts via two major classes of receptors, D1-type and D2-type. D1 receptors are highly expressed in the striatum and can also be found in the cerebral cortex. Here we review the role of D1 dopamine signaling in two major domains: L-DOPA-induced dyskinesias in Parkinson’s disease and cognition in neuropsychiatric disorders. While there are many drugs targeting D2-type receptors, there are no drugs that specifically target D1 receptors. It has been difficult to use selective D1-receptor agonists for clinical applications due to issues with bioavailability, binding affinity, pharmacological kinetics, and side effects. We propose potential therapies that selectively modulate D1 dopamine signaling by targeting second messengers downstream of D1 receptors, allosteric modulators, or by making targeted modifications to D1-receptor machinery. The development of therapies specific to D1-receptor signaling could be a new frontier in the treatment of neurological and psychiatric disorders.